GE_GERICHTE C/11532/2013 vom 8. November 2016 - GE Cour de justice (2016)
CONTRAT INDIVIDUEL DE TRAVAIL ; RÉSILIATION ABUSIVE ; RÉSILIATION IMMÉDIATE ; JUSTE MOTIF ; INDEMNITÉ(EN GÉNÉRAL) | CO.336; CO.337; CO.337c